2020
DOI: 10.1186/s13068-020-01673-4
|View full text |Cite
|
Sign up to set email alerts
|

The H2O2-dependent activity of a fungal lytic polysaccharide monooxygenase investigated with a turbidimetric assay

Abstract: Background: Lytic polysaccharide monooxygenases (LPMOs) are copper-dependent redox enzymes that cleave recalcitrant biopolymers such as cellulose, chitin, starch and hemicelluloses. Although LPMOs receive ample interest in industry and academia, their reaction mechanism is not yet fully understood. Recent studies showed that H 2 O 2 is a more efficient cosubstrate for the enzyme than O 2 , which could greatly affect the utilization of LPMOs in industrial settings. Results:We probe the reactivity of LPMO9C from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 58 publications
(103 reference statements)
3
64
0
Order By: Relevance
“…As recent studies reported that LPMOs are more efficient when fueled with H 2 O 2 as co-substrate instead of O 2 [ 18 , 28 , 57 , 58 ], we assessed the suitability of H 2 O 2 as co-substrate for Taus LPMO9B. First, PASC was incubated with Taus LPMO9B, H 2 O 2 and an excess of reductant (1-mM ascorbic acid).…”
Section: Resultsmentioning
confidence: 99%
“…As recent studies reported that LPMOs are more efficient when fueled with H 2 O 2 as co-substrate instead of O 2 [ 18 , 28 , 57 , 58 ], we assessed the suitability of H 2 O 2 as co-substrate for Taus LPMO9B. First, PASC was incubated with Taus LPMO9B, H 2 O 2 and an excess of reductant (1-mM ascorbic acid).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, addition of fresh AscA will lead to increased generation of H 2 O 2 . Increased formation of H 2 O 2 would normally speed up the reaction, since H 2 O 2 is a good co-substrate for LPMOs [ 20 , 25 , 28 ]. However, in this case, one could envisage a situation where too much H 2 O 2 is produced due to excess AscA, which can damage the LPMO.…”
Section: Discussionmentioning
confidence: 99%
“…LPMO catalysis has generally been thought to be strictly dependent on molecular oxygen and a reductant that delivers two electrons and two protons for each catalytic cycle [9,23,24]. However, recent studies on LPMOs belonging to families AA9 and AA10, have shown that H 2 O 2 can drive LPMO reactions, and that these reactions are orders of magnitude faster than O 2 -driven reactions [20,[25][26][27][28][29]. The peroxygenase driven reaction only requires sub-stoichiometric amounts of reductant for an initial, "priming", reduction of the LPMO, after which the enzyme can catalyze multiple reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Perna et al showed that the observed effect is due to increased H 2 O 2 -production by reactions involving laccase-modified lignin [269]. For the successful exploitation of these effects in biomass conversion, however, further research is needed, addressing, for example, the interaction of lignin-active oxidoreductases with lignin, as well as the actual flow of electrons, the [67,104,180,190,330], 9F [180,190,335], 9E, and 9J [180,190] from N. crassa and PsAA9A and 9B from Pestalotiopsis sp. [263] NcCDH IIB + NcAA9C [180,190,330], 9E, 9F, and 9J [180,190] from N. crassa [190] Pyranose dehydrogenase (PDH), PQQ-dependent AA12 [266,312] Catalase from C. glutamicum…”
Section: Other Oxidoreductases In Biomass Conversionmentioning
confidence: 99%
“…from N. crassa [104] The tested enzyme pairs and the (putative) modes of interaction between them are listed for each type of oxidoreductase a The role and nature of the reduction step differs between catalytic scenarios, as outlined in the main text and Fig. 3 [37].…”
Section: Other Oxidoreductases In Biomass Conversionmentioning
confidence: 99%